2005
DOI: 10.1021/ja054955z
|View full text |Cite
|
Sign up to set email alerts
|

Collective Behavior of Franck−Condon Excited States and Energy Transfer in DNA Double Helices

Abstract: Absorption of UV radiation by DNA bases is known to induce carcinogenic mutations. The lesion distribution depends on the sequence around the hotspots, suggesting cooperativity between bases. Here we show that such cooperativity may intervene at the very first step of a cascade of events by formation of Franck-Condon states delocalized over several bases and subsequent energy transfer faster than 100 fs. Our study focuses on the double helix poly(dA).poly(dT), whose fluorescence, induced by femtosecond pulses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
218
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(244 citation statements)
references
References 18 publications
23
218
2
1
Order By: Relevance
“…After femtosecond excitation at 267 nm, we detected fluorescence at various wavelengths, over a large time-domain by means of two different techniques, fluorescence upconversion and time-correlated single photon counting. 11,12 These time-resolved data, associated with the steady-state absorption and fluorescence spectra, lead to the conclusion that the Franck-Condon excited states are delocalized over several bases, in line with results from circular dichroïsm performed on duplexes containing the same base sequence. 13,14 The initial low value and subsequent decrease of fluorescence anisotropy observed for poly(dA).poly(dT), on the subpicosecond time-scale, 11 when molecular motions 4 18/02/2010 are hindered, proved that energy transfer takes place among the bases in less than 100 fs via intraband scattering.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…After femtosecond excitation at 267 nm, we detected fluorescence at various wavelengths, over a large time-domain by means of two different techniques, fluorescence upconversion and time-correlated single photon counting. 11,12 These time-resolved data, associated with the steady-state absorption and fluorescence spectra, lead to the conclusion that the Franck-Condon excited states are delocalized over several bases, in line with results from circular dichroïsm performed on duplexes containing the same base sequence. 13,14 The initial low value and subsequent decrease of fluorescence anisotropy observed for poly(dA).poly(dT), on the subpicosecond time-scale, 11 when molecular motions 4 18/02/2010 are hindered, proved that energy transfer takes place among the bases in less than 100 fs via intraband scattering.…”
Section: Introductionsupporting
confidence: 74%
“…(dT) 20 and the poly(dA).poly(dT) spectra in Figure 1 is representative of their relative fluorescence quantum yield which is higher by 15 ± 5% for the oligomer than for the polymer (3x10 -4 ). 11 This difference arises from the fact that the oligomer spectrum is more intense than that of polymer at its red side. In order to describe the decays in a quantitative way and compare them to the decays of poly(dA).poly(dT), 11 we performed for both duplexes a non-linear fitting/deconvolution procedure using bi-exponential functions,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It has also been reported that, in contrast to 2'deoxyadenosine, only two photon ionization was observed upon irradiation of thymidine aqueous solutions by 193 nm laser pulses. Finally, (dA) n strands are known to stack better 28 than (dT) n strands 29,30 and base stacking is expected to promote the decrease of IP.The quantum yield for one photon ionization φ 1hν found from the plots in Figure 2 is (1.1 ± 0.1)x10 These values are comparable to the quantum yield found for the formation of (6-4) thymine dimers in (dT) 20 . 19 The φ 1hν of all three oligomers is higher by at least one order of magnitude compared to that of dAMP, demonstrating that organization of the bases in single and double helices leads to a lowering of the ionization potential.…”
supporting
confidence: 50%
“…18 In contrast, the lifetimes of the excited states of small oligomers or DNA itself are larger by several orders of magnitude. Excitonic and charge transfer states have been made responsible for this difference, and the role of these states has been discussed extensively on the basis of experimental 2,3,[15][16][17][19][20][21][22][23][24][25] and theoretical 14,24,[26][27][28] work. Most theoretical ab initio approaches on the excited states of DNA have considered small polymers, for which the excited states are calculated using time-dependent density functional theory 24,[26][27][28] (TD-DFT) or wave function based methods.…”
Section: Introductionmentioning
confidence: 99%